2017
DOI: 10.1111/are.13373
|View full text |Cite
|
Sign up to set email alerts
|

Motility of sea urchin Paracentrotus lividus spermatozoa in the post-activation phase

Abstract: The characterization of sperm motility patterns, particularly post‐activation changes, is the first step in setting up species‐specific protocols involving gamete management and embryo production, for both aquaculture and laboratory research purposes. This study is aimed at the characterization of the sperm motility pattern of the purple sea urchin Paracentrotus lividus. Semen samples were individually diluted in artificial sea water for sperm motility activation. They were then incubated at 18°C for up to 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Because the sperm concentration of fresh semen was nearly double that of frozen semen (Table 2), the fresh sperm control group may have contained too much sperm, resulting in poor water quality and affecting embryo growth. This may explain the suboptimal fertilization and hatchability results in the fresh sperm treatment group (Adams et al, 2004;Fabbrocini and D'adamo, 2017). In future studies, we will optimize the sperm-egg ratio for fresh sperm and frozen sperm and determine how to prolong and maintain the quality of sea cucumber eggs.…”
Section: Fertilization Rate and Hatching Ratementioning
confidence: 99%
“…Because the sperm concentration of fresh semen was nearly double that of frozen semen (Table 2), the fresh sperm control group may have contained too much sperm, resulting in poor water quality and affecting embryo growth. This may explain the suboptimal fertilization and hatchability results in the fresh sperm treatment group (Adams et al, 2004;Fabbrocini and D'adamo, 2017). In future studies, we will optimize the sperm-egg ratio for fresh sperm and frozen sperm and determine how to prolong and maintain the quality of sea cucumber eggs.…”
Section: Fertilization Rate and Hatching Ratementioning
confidence: 99%
“…Linhart et al (2005) (Figueroa et al 2016), 97 µm s -1 to 134 µm s -1 in Prochilodus lineatus (Viveiros and Leal 2016;Viveiros et al 2017), 57 µm s -1 in rainbow trout Oncorhynchus mykiss (Suquet et al 2012b) and µm s -1 in Siberian sturgeon Acipenser baerii spermatozoa (Sarosiek et al 2014). VSL of sea urchin spermatozoa was shown to be 170-240 µm sec -1 in Hemicentrotus pulcherrimus (Hiramoto and Baba 1978) and 150-200 µm sec -1 in Paracentrotus lividus (Fabbrocini and D'Adamo 2017). The factors contributing to the relatively low velocity observed for black-lip pearl oyster in our study may be twofold: firstly, the activation of oyster sperm motility and its duration is associated with internal concentration of cAMP (Demoy-Schneider et al 2014) under internal pH control (Boulais et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…In particular, compared to sperm activated at pH 8.1, in those exposed to acidification, a 6% reduction in the speed (equal to 20 µm/s) and 9% in the number of motile sperm were observed. The 0-5 time interval is important considering that in other species, under laboratory conditions, the majority of fertilization episodes happen within this time range [91], and despite optimal conditions, fertilization ability in P. lividus is maintained for longer [92]. In another marine invertebrate, the madrepora Acropora digitifera, Nakamura, and Morita [40] found that the percentage of motile spermatozoa decreased by 36.5% when comparing preindustrial levels of pCO 2 (300 ppm = pH 8.1) with those expected for the end of this century (1000 ppm = pH 7.7).…”
Section: Discussionmentioning
confidence: 99%